1975
DOI: 10.1002/macp.1975.021761118
|View full text |Cite
|
Sign up to set email alerts
|

A radiochemical study of the Ziegler‐Natta catalysed polymerization of styrene

Abstract: The polymerization of styrene in benzene solution was studied at 60°C using a catalyst composed of a-titanium trichloride and [ ''C]triethylaluminium. The results obtained showed that the use of this system to measure the number of active sites on the catalyst is an unreliable method likely to over-estimate the number manifold. Isotope dilution experiments indicated that the contamination was due to the formation of both free and bound [ ''C]polyethylene. Use of tritiated methanol as a quenching agent to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In particular, Ayrey et al 4 have made a detailed study of the use of labeled triethylaluminium and have shown that for styrene the contamination is very substantial, leading to an apparent number of ethyl groups per polymer chain (n,) in the range 5.6-60, even under normal polymerization conditions. Since the basis of the method4 precludes values of n, > 1, the above result apparently invalidates the use of labeled cocatalysts for the determination of active-center concentrations.…”
mentioning
confidence: 99%
“…In particular, Ayrey et al 4 have made a detailed study of the use of labeled triethylaluminium and have shown that for styrene the contamination is very substantial, leading to an apparent number of ethyl groups per polymer chain (n,) in the range 5.6-60, even under normal polymerization conditions. Since the basis of the method4 precludes values of n, > 1, the above result apparently invalidates the use of labeled cocatalysts for the determination of active-center concentrations.…”
mentioning
confidence: 99%